New Landscapes in the City, or Learning from Landscape - Engel, Barbara (project baikal, 2016)
The article considers new forms of relationship between city and landscape. It also reveals one of the major challenges for planning and urban governance: to use the creative potential which is formed in different pioneering or temporary uses and activities of people for sustainable development of the urban environment.